The Impact of Official Development Aid on Maternal and Reproductive Health Outcomes: A Systematic Review - Taylor, Emma Michelle; Hayman, Rachel; Crawford, Fay; Jeffery, Patricia; Smith, James (PLOS ONE, 2013)
Background Progress toward meeting Millennium Development Goal 5, which aims to improve maternal and reproductive health outcomes, is behind schedule. This is despite ever increasing volumes of official development aid targeting the goal, calling into question the distribution and efficacy of aid. The 2005 Paris Declaration on Aid Effectiveness represented a global commitment to reform aid practices in order to improve development outcomes, encouraging a shift toward collaborative aid arrangements which support the national plans of aid recipient countries (and discouraging unaligned donor projects). Methods and Findings We conducted a systematic review to summarise the evidence of the impact on MDG 5 outcomes of official development aid delivered in line with Paris aid effectiveness principles and to compare this with the impact of aid in general on MDG 5 outcomes. Searches of electronic databases identified 30 studies reporting aid-funded interventions designed to improve maternal and reproductive health outcomes. Aid interventions appear to be associated with small improvements in the MDG indicators, although it is not clear whether changes are happening because of the manner in which aid is delivered. The data do not allow for a meaningful comparison between Paris style and general aid. The review identified discernible gaps in the evidence base on aid interventions targeting MDG 5, notably on indicators MDG 5.4 (adolescent birth rate) and 5.6 (unmet need for family planning). Discussion This review presents the first systematic review of the impact of official development aid delivered according to the Paris principles and aid delivered outside this framework on MDG 5 outcomes. Its findings point to major gaps in the evidence base and should be used to inform new approaches and methodologies aimed at measuring the impact of official development aid.